DEVELOP THE SECRETS OF FORMING A PERFECT MEMORY AND REMEMBERING IN EDUCATION - Mahfuza Husenovna Sadullayeva (European Science Publishing, 2024)
This article will highlight the methods of using mnemotechnical methods in the organization of educational processes in the higher education system and the formation of perfect memory in itself. A number of techniques and techniques of different methods have been touched upon in creating perfect memory. The memory reveals the process of constant memory of historical data, their analysis by historical events and phenomena, persons and deadlines. Qualitative education, interventional educational tools and individual educational technologies are important in the development of memory skills and in the expansion of the field of teaching in the historical sciences processes, the listener and the ways to eliminate the problems associated with the existing memory on the scientific view, and techniques reflected.
Keywords: innovative, interactive, cognitive, philosopher, philosophical, classical experience, mnemonics, Melon culture, trend, visual, mnemotechnics.